VD_FINDINFO ML / 2009 / 99 vom 7. Mai 2009 - VD Tribunal cantonal (2009)
RECONNAISSANCE DE LA DÉCISION, CONVENTION{SIGNIFICATION ET NOTIFICATION DES ACTES JUDICIAIRES}, NOTIFICATION IRRÉGULIÈRE | 27 ch. 2 CL, 34 CL, 80 LP, 81 al. 3 LP